Zinc sulfide as a solid phase additive for improving the processing characteristics of ferrihydrite residues - Richmond, William; Loan, Mitch; Parkinson, Gordon; Newman, M. (Elsevier Science BV, 2005)
The effect of ZnS powders as additives for improving the physical and chemical properties of ferrihydrite residues has been studied in both kinetic and batch experiments. Four ZnS samples were compared: two industrial ZnS concentrates, high purity ZnS pieces, and a sample of synthetic ZnS nanoparticles. The industrial ZnS concentrates were found to be the most effective for promoting the transformation of ferrihydrite to hematite, and this effect was found to be due to their lower surface charge at pH 3, which promotes formation of mixed ZnS/ferrihydrite aggregates. For the high purity ZnS samples, aggregation was not favoured, and only goethite formation was promoted. The effect of particle size of the ZnS additive was also studied, and it was found that samples of smaller average particle size were more effective in promoting phase transformation. Measurement of filtration times and moisture content of ferrihydrite residues precipitated in the presence of ZnS showed only minor improvement in physical handling and indicated that better control of surface properties of the additive would be needed to optimise its effect on phase transformation.